(8x 2 −15x)−(x 2 −27x)=ax 2 +bxleft parenthesis, 8, x, squared, minus, 15, x, right parenthesis, minus, left parenthesis, x, squ
quester [9]
Answer:
<h2>5</h2>
Step-by-step explanation:
Given the expression (8x² −15x)−(x² −27x) = ax² +bx, we are to determine the value of b-a. Before we determine the vwlue of b-a, we need to first calculate for the value of a and b from the given expression.
On expanding the left hand side of the expression we have;
= (8x² −15x)−(x² −27x)
Open the paranthesis
= 8x² −15x−x²+27x
collect the like terms
= 8x²−x²+27x −15x
= 7x²+12x
Comparing the resulting expression with ax²+bx
7x²+12x = ax²+bx
7x² = ax²
a = 7
Also;
12x = bx
b =12
The value of b - a = 12 - 7
b -a = 5
Hence the value of b-a is equivalent to 5
Answer:
4x - 7
Step-by-step explanation:
x + 2x + 3x - 2x = 4x
-8 + 1 = -7
Answer:
50?
Step-by-step explanation:
I said 50 because there were 60 na butterflies so there was probably 50.
I am sorry if this wrong tho
ah, those are systems you want one variable to cancel out. I would time the bottom equation by -1 so x cancels then u solve for y. then u plug all back in to solve for x.